(untitled) (Ustozlar uchun, 2026)
This study examines the difficulties that Uzbek learners face when using English perfect tenses. Many students find these tenses difficult to understand because such structures do not exist in the Uzbek language. Learners often use auxiliary verbs like "have" and "had" incorrectly or omit them completely, and they also confuse the present perfect with the past simple tense. They make mistakes when using time expressions such as "since," "for," and "already." The results show that these problems are common among learners. The study suggests that more practice, clear explanations, and real-life examples can help students better understand perfect tenses.